Prospects of the development of the solar energy industry in the Caribbean. (1st January 2012) - Charles, Don
The Caribbean region is a chain of small islands that are vulnerable to the negative impacts of climate change and high oil prices. Renewable energy, or more specially, solar energy can provide a solution to both of these challenges for the Caribbean. Yet despite the positive impact solar energy can have upon the Caribbean, not much is being done to commerciality develop the solar energy industry for electricity generation. This study reviews the barriers (economic, legal and technical) that prevent the development of the solar energy industry in the Caribbean. This study also explores the incentives that can be used to stimulate the solar energy industry in the Caribbean for electricity generation.